Human Body Factory - Dan Green (London Macmillan Children's Books, 2014)
An entertaining and informative exploration of the busy human body factory, from the MD sending out orders in the brain to waste being sorted and delivered out of the body. With each 'department' introduced by the busy workers who keep everything running smoothly, the ingenious artworks are packed with humorous details, all backed up with fascinating facts and accessible text describing and explaining the body's processes. You'll find plenty to amaze and amuse in this comprehensive, fact-filled guide to the human body.